Economics - Parkin, Michael 1939-; Powell, Melanie; Matthews, Kent 1952- (Pearson, 2022)
"Thoroughly updated, this revision builds on the solid foundation of the previous edition and retains its thorough and detailed presentation of the principles of economics, its emphasis on real-world examples and applications, its development of critical thinking skills, its diagrams renowned for pedagogy and precision, and its path-breaking technology. Most chapters have been thoroughly reworked to achieve even greater clarity and to place greater emphasis on applications to current issues. Some sections of chapters have been removed and other sections added to cover new issues, particularly those that involve current policy problems. Current issues organise each chapter. News stories about today's major economic events tie each chapter together, from new abbreviated chapter-opening vignettes to Economics in the News and end-of-chapter problems and applications and online practice. Economics in the News boxes show students how to use the economic toolkit to understand the events and issues they are confronted with in the media. At Issue boxes show two sides of a controversial issue and helps students to apply the economic way of thinking to clarify and debate the issues. Among the many issues covered in one or more of the features described above are: Capitalism and its critics in Chapter 1 The supply elasticity of face masks in Chapter 4 Toilet paper price gouging in Chapter 5 The expansion of video streaming in Chapter 8 Climate change and wind power in Chapters 2 and 16 Brexit and Covid effects on UK growth in Chapter 26 Inflation risk in the EU in Chapter 28 Fiscal stimulus in Chapter 29 The Bank of England's extraordinary actions in Chapter 30 Extraordinary monetary stimulus in Chapter 30"--
Revised edition of the authors' Economics
Enthält Literaturangaben und Index
Keywords: Economics